(untitled) (Nueva Epoca, 2025)
The article analyzes the evolution of eco-abuse of rights in the ten years since the enactment of Argentina’s Civil and Commercial Code (CCC), highlighting its role within the so-called eco-code. Sozzo argues that the CCC redefined the concept of abuse of rights by extending it to collective environmental rights, thus incorporating an ecological function into individual rights. The paper explores the doctrinal foundations of this figure, its comparative development—particularly in the Civil Codes of China, Vietnam, and Bolivia—and its reception in Argentine case law. Through a critical assessment, the author concludes that the judicial use of eco-abuse remains limited, mainly due to the persistence of a legal culture dominated by rigid rules instead of open-ended clauses. Finally, the article offers methodological guidelines to enhance the application of eco-abuse of rights and to distinguish it from external conflicts between individual and collective rights, as well as from breaches of the duty to prevent or repair harm.